DNA Detection Reveals Mycobacterium tuberculosis Complex Shedding Routes in Its Wildlife Reservoir the Eurasian Wild Boar. Issue 3 (14th December 2015) - Barasona, J. A.; Torres, M. J.; Aznar, J.; Gortázar, C.; Vicente, J.
Summary: Since the intensity and frequency of pathogen shedding by hosts determine the probability of infection through direct and indirect contact, the shedding characterization of Mycobacterium tuberculosis complex (MTC) in the key host reservoir in Iberia, the Eurasian wild boar ( Sus scrofa ), is crucial. We aimed (i) to describe the natural shedding routes of MTC in free‐ranging wild boar by a new semi‐automated PCR method and (ii) to determine the association of MTC shedding pattern with tuberculosis (TB) progression and individual factors. MTC shedding (by any of the possible routes) was detected in a total of 30.8% (±7.5) out of the sampled individuals with valid or interpretable test results ( n = 39). The proportion of TB‐positive shedders according to the route was 13.6% (±7.5) for oral swabs, 4.5% (±4.5) for nasal swabs, 4.5% (±4.4) for faecal swabs and 13.6% (±7.5) for individuals being positive to all swabs concomitantly. The probability of shedding mycobacteria (by any route) statistically associated with TB generalization, and the TB score was significantly higher in individuals testing positive to at least one route compared to negatives. Overall, a diversity of shedding routes in wild boar is possible, and it is remarkable that for the first time, the faecal shedding is confirmed for naturally infected wild boar. Our results are consistent with the role wild boar plays for TB maintenance in host communities and environments in Iberia and confirm that it is an important source of mycobacteria infection by different routes. Finally, we evidenced the use of a new PCR technique to detect MTC DNA in excretions can be practical and defined the target routes for sampling wild boar shedding in future studies, such as interventions to control TB in wild boar that can be measured in terms of impact on mycobacteria excretion and transmission (i.e. vaccination).